Organizational Culture in Construction: An Investigation of Trends and Practices in Large-Size Construction Companies - Putra, Arya Pradamansyah; Negara, Kartika Puspa; Anwar, M Ruslin (ASTONJADRO, 2025)
Construction companies are one of the business sectors that drive the Indonesian economy. The increase in construction companies has led to increased competition in the industry. Culture influences the construction process that applies to the company and the output of construction products. This study aims to find out how organizational culture practices and trends in the large-size construction companies. To investigate the organizational culture practices and trends, the literature study was used to develop a framework and the Competing Values ​​Framework (CVF) through the Organizational Culture Assessment Instrument (OCAI) was adopted. The framework is also extended for each culture type, which are clan, adhocracy, hierarchy, and market into six-key dimensions. The population in this study was 26 large-size construction companies in East Java. The organizational culture practices results found that the dimensions of employee participation, innovation culture, reward, punishment, and teamwork orientation still need to be fully implemented (level 3). Meanwhile, the performance emphasis factor has been fully implemented (level 4). Furthermore, the trend of companies’ culture types is clan culture, where the dominance of cultural types from the strongest to the weakest are clan, market, hierarchy, and adhocracy, with values of 27.51, 26.35, 24.87, and 21.27 respectively. This observation contributes to enriching the study of organizational culture in construction area.